Oral creatine supplementation - Juhn, M. S. (The Physician and Sportsmedicine, 1999)
Many athletes--especially those participating in sports that emphasize strength--are taking oral creatine. Creatine supplements appear to enhance performance in repeated short bursts of stationary cycling and weight lifting, but the data on running, swimming, and single cycle sprints are not convincing of an ergogenic effect. Commonly reported side effects include muscle cramping, GI disturbances, and renal dysfunction, but creatine's effect on the heart, brain, reproductive organs, and other organs has yet to be determined. Comprehensive studies with larger samples and crossover design are needed. If patients decide to take oral creatine, physicians need to provide guidance for proper dosing as well as education about potential harmful effects.